Microseismicity and Lava Flows Hint at Magmato‐Tectonic Processes Near the Southern Tip of the Fonualei Rift and Spreading Center in the Lau Basin. Issue 4 (27th April 2021) - Schmid, F.; Cremanns, M.; Augustin, N.; Lange, D.; Petersen, F.; Kopp, H.
Abstract: Spreading centers in the proximity of back‐rolling subduction zones constitute an ideal natural laboratory to investigate the interaction of magmatism and tectonism during the early evolution of back‐arc basins. Using 32 days of ocean bottom seismometer data, we located 697 micro‐earthquakes at the southern Fonualei Rift and Spreading Center (S‐FRSC). The majority of epicenters concentrate along the central region of the axial valley, marking the active ridge axis. Only odd events were associated with the prominent faults bounding the axial valley. About 450 events are spatially clustered around 17°42′S and their waveforms show a pronounced similarity. Most of these events are associated with a 138 h lasting earthquake swarm. The tectonic structure of the ridge axis in the S‐FRSC resembles a series of left‐stepping en echelon segments, expressed at the seafloor by numerous volcanic ridges. The recorded earthquake swarm is located at the stepover of two en echelon segments suggesting that the earthquake swarm is mainly tectonically driven. The events directly beneath our seismic network indicate a maximum depth of brittle faulting down to about 14 km below the seafloor. This is within the maximum depth range of brittle faulting at ultraslow mid‐ocean ridges. Since the thickness of the brittle lithosphere is mainly controlled by temperature, our results suggest a sub‐axial thermal structure similar to that of ultraslow mid‐ocean ridges of similar opening rates. Key Points: Microseismicity is focused in the axial valley along the spreading axis and coincides with volcanic ridges and lava flows An earthquake swarm is located at the stepover of two en echelon segments. The swarm is mainly controlled by tectonism The brittle axial lithosphere is about 14 km thick, which is in agreement with mid‐ocean ridges of similar spreading rates